Comunidad boliviana de Córdoba Caracterización 1996 y proceso migratorio - DOMENACH,Hervé (UNIVERSIDAD NACIONAL DE CORDOBA, 1998)
ALVAREZ, María; BOLOGNA, Eduardo; CARBONETTI, Adrián; LOPEZ GARERI, Valeria; MASCIARDI, Viviana; PERALTA, Pedro